Design: UI/UX Penjualan Telur Ayam di Cilacap dengan Metode R&D - Muhammad Agus Saputra; Aini Ahofi Achanti (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Nowadays, more and more e-commerce platforms are emerging, creating a highly competitive environment for both individuals and groups. User experience and interface are key factors in attracting users' attention and fulfilling various needs to survive in a crowded market. In this context, the author proposes the prototyping of a chicken egg sales application named EiTech Supply in Cilacap Regency. This application is designed to overcome the problems that chicken egg farmers often face, such as competition between regions and the entry of new farmers with very low prices to attract customers. With the EiTech Supply application, it is expected to reduce these problems and increase the competitiveness of chicken egg farmers both inside and outside the region.